2014
DOI: 10.1002/hipo.22331
|View full text |Cite
|
Sign up to set email alerts
|

Objects and landmarks: Hippocampal place cells respond differently to manipulations of visual cues depending on size, perspective, and experience

Abstract: Human navigation studies show that landmarks are used for orientation, whereas objects contribute to the contextual representation of an environment. What constitutes a landmark? Classic rodent studies show that hippocampal place fields are controlled by distal, polarizing cues. Place fields, however, are also influenced by local cues. One difficulty in examining mechanisms by which distal and local cues influence the activity of hippocampal cells is that distant cues are necessarily processed visually, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…Moreover, our model is also in line with the elevated sensitivity of the neuronal responses to any change in the environment (e.g. the delivery of reward (12,58), or the manipulation of landmarks (59,60)). This phenomenon is often described as "remapping" (61) and is widely observed in experiments.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, our model is also in line with the elevated sensitivity of the neuronal responses to any change in the environment (e.g. the delivery of reward (12,58), or the manipulation of landmarks (59,60)). This phenomenon is often described as "remapping" (61) and is widely observed in experiments.…”
Section: Discussionsupporting
confidence: 71%
“…The PER provides this information to the hippocampus for associative learning, for example, when a particular object is rewarded in one context but not another. Indeed, a number of studies have reported that the hippocampus responds to objects as well as places, contexts, and landmarks (Komorowski et al, 2009;Deshmukh and Knierim, 2013;Scaplen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Place field responses within a condition were classified as rotation, remap or no change as previously described (Scaplen et al, 2014). Briefly, place fields were classified as having predictably rotated if the field rotated at least once in concert with the rotation of the relevant cue.…”
Section: Methodsmentioning
confidence: 99%